Analisi Inovasi Produk Kreatif Ecobrick sebagai Green Economy dalam Perspektif Etika Produksi Islam - Prasetyo, Agung; Sukamto; Dayat, M. (Kartika: Jurnal Studi Keislaman, 2025)
This study analyses ecobrick creative product innovation as a green economy in the perspective of Islamic production ethics with a case study in Ambal Ambil Village, Pasuruan. This research is motivated by the unrest arising from the increasing plastic waste but still low management of the plastic waste problem which indicates that the level of recycling of plastic waste by the community in Indonesia is still low. The selection of Ambal Ambil Village as the object of research because this village applies solutions related to the problem of plastic waste into creative ecobrick products. The purpose of the research is to study, analyse, and identify methods, efficiency techniques, the application of Islamic production ethics, as well as the level of awareness and community participation in environmental sustainability and local economic empowerment. This research method uses qualitative research with a phenomenological approach. This study shows that ecobricking is able to reduce the volume of plastic waste in the community and reduce the impact of environmental pollution, thus contributing to environmental sustainability. On the other hand, ecobrick management is conducted transparently and holds the principles of Islamic production ethics for the common good. The implementation of ecobricking involves the participation of the community of Ambal Ambil Village, which has the effect of increasing public awareness of not littering. This research contributes to supporting ecobricks as a creative solution to the plastic waste problem